2023
DOI: 10.3390/ma16051776
|View full text |Cite
|
Sign up to set email alerts
|

Shortwave Ultraviolet Persistent Luminescence of Sr2MgSi2O7: Pr3+

Abstract: Currently, extensive research activities are devoted to developing persistent phosphors which extend beyond the visible range. In some emerging applications, long-lasting emission of high-energy photons is required; however, suitable materials for the shortwave ultraviolet (UV–C) band are extremely limited. This study reports a novel Sr2MgSi2O7 phosphor doped with Pr3+ ions, which exhibits UV–C persistent luminescence with maximum intensity at 243 nm. The solubility of Pr3+ in the matrix is analysed by X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…The choice of active Pr3+ ion concentrations in SCMS glasses is determined by a tradeoff between the praseodymium absorption qualities, especially at the excitation wavelength of 445 nm, and the ability to measure the up-conversion spectra of the material in the ultraviolet region as well as an emission in a wide spectral range. The ionic radii of the involved ions are the following: Mg 2+ (0.66 Å), Ca 2+ (0.99 Å) [17], (0.94 Å [11]), Pr 3+ (1.126 Å) [18], and Sr 2+ (1.260 Å [18]).…”
Section: Methodsmentioning
confidence: 99%
“…The choice of active Pr3+ ion concentrations in SCMS glasses is determined by a tradeoff between the praseodymium absorption qualities, especially at the excitation wavelength of 445 nm, and the ability to measure the up-conversion spectra of the material in the ultraviolet region as well as an emission in a wide spectral range. The ionic radii of the involved ions are the following: Mg 2+ (0.66 Å), Ca 2+ (0.99 Å) [17], (0.94 Å [11]), Pr 3+ (1.126 Å) [18], and Sr 2+ (1.260 Å [18]).…”
Section: Methodsmentioning
confidence: 99%
“…[31][32][33] Moreover, Si-based melilites doped with different rare earth elements exhibit ultraviolet (UV) persistent luminescent properties after UV or X-ray excitation. [34][35][36][37][38][39] Datolite and homilite Ca 2 Fe 2+ B 2 Si 2 O 8 O 2 are members of the datolite subgroup of the gadolinite mineral group with the general formula A 2 MQ 2 Si 2 O 8 ϕ 2 , where A-Ca, Y and lanthanides, M-Fe 2+ or vacancy, Q-B or Be, ϕ-O or OH. 40 Both datolite and homilite have a relatively simple chemical composition, consisting of elements common in the Earth's crust.…”
Section: Introductionmentioning
confidence: 99%
“…Although the magnetic properties of silicate members of this structural family have not been studied in detail, it has recently been shown that the substitution of Ge for Si can also be very promising 31–33 . Moreover, Si‐based melilites doped with different rare earth elements exhibit ultraviolet (UV) persistent luminescent properties after UV or X‐ray excitation 34–39 …”
Section: Introductionmentioning
confidence: 99%